The Influence of School Leadership and Academic Supervision on Teachers’ Professional Competence - Mokhamad Abidin Adham; Yovitha Yuliejantiningsih; Titik Haryati (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
This study investigates the influence of school leadership and academic supervision on teachers’ professional competence in public high schools in Batang District, Central Java. Using a quantitative approach with survey methods and linear regression analysis, the research involved 85 teachers selected through proportional random sampling. The findings reveal that school leadership significantly affects teachers’ professional competence (Sig. = 0.000; effect size = 71.4%), as does academic supervision (Sig. = 0.000; effect size = 64.7%). Combined, both variables also exert a significant influence (Sig. = 0.000; effect size = 66.2%). These results underscore the importance of effective leadership particularly in fostering innovation—and robust academic supervision, especially in evaluation and follow-up, in enhancing professional competence. The study recommends that school leaders strengthen these areas and collaborate with teachers to support professional growth. Teachers are also encouraged to deepen subject mastery and adopt more effective teaching strategies to improve instructional quality and student learning outcomes.